2019
DOI: 10.5586/aa.1769
|View full text |Cite
|
Sign up to set email alerts
|

Photosynthetic performance of young maize (Zea mays L.) plants exposed to chilling stress can be improved by the application of protein hydrolysates

Abstract: Biostimulants offer a novel approach for the regulation of crucial physiological processes in plants. Recently, it has been observed that the application of biostimulants on both seeds and plants may ameliorate to some extent the negative effects of abiotic stresses such as drought, heat, salinity, and others. In the climate conditions of Bulgaria, the early developmental stages of warm climate crops, like maize, often occur under suboptimal temperatures. Although the mitigation of abiotic stress is perhaps th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 32 publications
1
7
0
Order By: Relevance
“…In addition, our study demonstrated that the pretreatment of the cucumber plants with the biostimulant Naturamin WSP alleviated, to some extent, the negative effects of chilling stress on plant growth (Table 1) and affected several biochemical parameters (Table 2-Table 5). ese observations corroborate the results of Botta (2013) and Cholakova-Bimbalova et al (2019), who reported a positive influence of foliar amino acid application on lettuce and maize plants exposed to chilling stress, respectively.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In addition, our study demonstrated that the pretreatment of the cucumber plants with the biostimulant Naturamin WSP alleviated, to some extent, the negative effects of chilling stress on plant growth (Table 1) and affected several biochemical parameters (Table 2-Table 5). ese observations corroborate the results of Botta (2013) and Cholakova-Bimbalova et al (2019), who reported a positive influence of foliar amino acid application on lettuce and maize plants exposed to chilling stress, respectively.…”
Section: Discussionsupporting
confidence: 90%
“…However, information regarding the effects of protein hydrolysates on plants exposed to chilling stress is very limited. Recently, Cholakova-Bimbalova et al (2019) reported that the application of a protein hydrolysate increased the photosynthetic performance of maize plants exposed to chilling stress. One possible explanation for the protective effects of protein hydrolysates is related to the role of free amino acids and low-molecular-weight peptides as signal molecules and precursors for essential metabolites.…”
Section: Introductionmentioning
confidence: 99%
“…Macro-and micro-nutrients amount in maize roots and shoots after 7 days under low N and treated with: CS extracts, MA, and their N-adjusted relative controls. derived protein hydrolysates [69] and when maize seedlings were treated with an animal protein hydrolysate containing free amino acids and small peptides [70]. In the case herein reported, maize plants were harvested in a juvenile state, where a possible positive effect of biostimulant in delaying senescence could not be assessed.…”
Section: Tablementioning
confidence: 99%
“…These compounds improve nutrient use efficiency and may ameliorate the negative effects of abiotic and biotic stresses to some extent [17,18]. In maize cultivation, the use of biostimulants helps to improve physiological processes, which results in obtaining a higher yield [19][20][21]. Among the secondary metabolites, many phenolic compounds confer tolerance to stress, especially flavonoids and phenolic acids, which are produced via the shikimate-phenylpropanoid biosynthetic pathway [22,23].…”
Section: Introductionmentioning
confidence: 99%